Models of Integrated School Development for the Contemporary Era - Supriyadi; Komarudin Sassi (CV. Creative Tugu Pena, 2025)
This article discusses the model of integrated school development in the contemporary era, characterized by the integration of spiritual, intellectual, and technological values within the education system. Integrated schools serve as a strategic alternative in addressing the challenges of 21st-century education, which demands that students possess balanced academic competence, character, and digital literacy. The research method used is a literature study with a descriptive-analytical approach. The findings show that the development of integrated schools emphasizes three main aspects: the integration of general and religious curricula, technology-based management, and the cultivation of an Islamic and innovative school culture. The study implies that educational policy should promote synergy between religious values and digital competencies to create adaptive, moderate, and globally competitive learners.